PENGARUH QUENCHING TERHADAP KEKERASAN MATERIAL BAJA JIS SUP 9 - Purnomo, Gito; Putri, Fenoria; Effendi, Sairul (Politeknik Negeri Sriwijaya, Indonesia, 2020)
JIS SUP 9 Steel is a medium carbon steel with chemical content of 0,544% C, 0,238% Si, 0,820% Mn, 0,0146% P, 0,0030% S, 0,754% Cr, 0,0102% Mo, 0,00665% Ni, 0,0390% Al, 0,0095% Co, 0,0156% Cu, 0,0142% Ti, 0,0011% Sn, 0,0022% As, 0,0039% Zr, 0,0039% Zr, 0,0036% Ce, 0.0022% Se, 0,0047% Te, 0,0402% Ta, 0.00021% B, 0,0012% Zn, 0,00053% La, 97,4% Fe. The carbon content allows the steel to be hardened by a heat treatment process, hardening and cooling media. The temperature variations used were 750 ℃, 800℃,900℃ with a holding time of 30 minutes and cooled using salt water, oil and vegetable oil. This study aims to determine the effect of hardening and quenching processes on the hardness of JIS SUP 9 steel. The test results data were analyzed using ANOVA with full factorial level design, main effect model design, and 3 replications assisted by Design-Expert software. From the hardness test, the maximum hardness value of 59.2 HRC was obtained from the hardening process with oil cooling media at a temperature of 800 ℃, while the minimum hardness value obtained from the brine cooling medium was 16.5 HRC at a temperature of 750 ℃. The results of the analysis revealed that the main factor that had the most influence on increasing the hardness of the test specimens was the brine quenching media factor with a contribution percentage of 98.93%. Meanwhile, the increasing factor of hardness in oil quenching media with a contribution percentage of 98.02% and quenching vegetable oil with a percentage contribution of 98.80%. Keywords: JIS SUP 9 Steel, Hardening, Quenching, ANOVA, Full Factorial